Stiffness and damping effects of the rhombic piezoelectric stack transducer with a negative capacitance shunt. (September 2019) - Yan, B; Zheng, W; Zhou, S; Wu, C
Abstract: The piezoelectric shunt damping (PSD) is widely utilized to control structural vibrations based on its damping performance. Unlike previous studies, this work considers the stiffness and damping effects of a rhombic piezoelectric stack transducer with a negative capacitance shunt. The piezoelectric shunt stiffness (PSS) and the PSD concepts are proposed and theoretically modelled to investigate the stiffness and damping performance. The piezoelectric stack transducer with a negative capacitance can achieve both negative and positive stiffnesses to tune the natural frequency of the host structure. The root locus methods are utilized to judge the stability of the system. Both numerical simulation and experimental results demonstrate that the negative stiffness and the positive stiffness of the system greatly depend on the negative capacitance, while the damping depends on the resistance.